Philip P. Arnold, The Urgency of Indigenous Values - Wright, Robin Michel (Journal for the study of religion, nature and culture, 2024)
Philip P. Arnold, The Urgency of Indigenous Values (Syracuse, NY: Syracuse University Press, 2023), 269 pp., $ 29.95 (e-book), ISBN: 978-0-8156-5690-6.